14‐Vertex Heteroboranes with 14 Skeletal Electron Pairs: An Experimental and Computational Study. Issue 30 (2nd June 2016) - Robertson, Alasdair P. M.; Beattie, Nicholas A.; Scott, Greig; Man, Wing Y.; Jones, John J.; Macgregor, Stuart A.; Rosair, Georgina M.; Welch, Alan J.
Abstract: Three isomers of [(Cp*Ru)2 C2 B10 H12 ], the first examples of 14‐vertex heteroboranes containing 14‐skeletal electron pairs, have been synthesized by the direct electrophilic insertion of a {Cp*Ru + } fragment into the anion [4‐Cp*‐4, 1, 6‐RuC2 B10 H12 ] − . All three compounds have the same unique polyhedral structure having an approximate Cs symmetry and featuring a four‐atom trapezoidal face. X‐ray diffraction studies could confidently identify only one of the two cage C atoms in each structure. The other C atom position has been established by a combination of i) best fitting of computed and experimental 11 B and 1 H NMR chemical shifts, and ii) consideration of the lowest computed energy for series of isomers studied by DFT calculations. In all three isomers, one cage C atom occupies a degree‐4 vertex on the short parallel edge of the trapezium. Abstract : Living on the edge : The first three examples of 14‐vertex heteroboranes with 14 skeletal electron pairs have been prepared and characterized by a combination of spectroscopic, crystallographic, and computational techniques. The compounds [(Cp*Ru)2 C2 B10 H12 ] all share a unique cluster structure featuring a trapezoidal face. Atom colors: C gray, B yellow, Ru blue.